An agent-based platform for the study of watersheds as coupled natural and human systems. (March 2017) - Tesfatsion, Leigh; Rehmann, Chris R.; Cardoso, Diego S.; Jie, Yu; Gutowski, William J.
Abstract: This study describes the architecture and capabilities of an open source agent-based Java platform that permits the systematic study of interactions among hydrology, climate, and strategic human decision-making in a watershed over time. To demonstrate the platform's use and capabilities, an application is presented in accordance with ODD protocol requirements that captures, in simplified form, the structural attributes of the Squaw Creek watershed in central Iowa. Illustrative findings are reported for the sensitivity of farmer and city social welfare outcomes to changes in three key treatment factors: farmer land-allocation decision method, farmer targeted savings, and levee quality effectiveness for the mitigation of city flood damage. Highlights: An open-source agent-based Java platform is developed for the study of watersheds as coupled natural and human systems. The platform permits study of interactions among hydrology, climate, and human decision-making in a watershed over time. A watershed application is presented in accordance with the ODD protocol. Findings are reported for sensitivity of farmer and city social welfare to changes in three key treatment factors. The three key treatment factors are: farmer land-allocation decision method; farmer savings target; and levee quality.